THE RELATIONSHIP BETWEEN GRADE 9 STUDENTS’ PERCEPTIONS OF ENGLISH CLASSROOM ENVIRONMENT AND PREFERNCES FOR ENGLISH LEARNING STRATEGIES IN YINSHENG MIDDLE SCHOOL IN KUNMING, YUNNAN PROVINCE, CHINA - Fan, Wenkai; Karnjanapun, Supit (Scholar: Human Sciences, 2022)
The purpose of this quantitative study was to determine the levels of perceptions of English classroom environment and preferences for English learning strategies and investigate if there were significant relationships between perceptions of English classroom environment in terms of relationship, personal development, and system maintenance and change dimensions and preferences for English learning strategies of Grade 9 students at Yinsheng Middle school in Kunming, Yunnan Province, China. The participants were Grade 9 92 students in the target school. The What is Happening in This Class? (WIHIC) questionnaire was used to measure the levels of perceptions of English classroom environment including three dimensions (relationship, personal development, and system maintenance and change dimensions) while The Strategy Inventory for Language Learning (SILL) questionnaire was used to measure the level of students’ preferences for English learning strategies. Results indicated that the level of Grade 9 students’ overall perception of English classroom in terms of three dimensions were positive while the level of Grade 9 students’ preferences for English learning strategies was strong. Pearson’s product moment correlation suggested that there were positive and significant relationships between Grade 9 students’ perception of English classroom environment both in terms of relationship and personal development dimensions and preference for English learning strategies. However, there was no significant relationship between Grade 9 students’ perceptions of English classroom environment in terms of system maintenance and change dimension with preferences for English learning strategies.